Synthesis of Pyridoclax Analogues: Insight into Their Druggability by Investigating Their Physicochemical Properties and Interactions with Membranes. (26th November 2019) - De Pascale, Martina; Iacopetta, Domenico; Since, Marc; Corvaisier, Sophie; Vie, Véronique; Paboeuf, Gilles; Hennequin, Didier; Perato, Serge; De Giorgi, Marcella; Sinicropi, Maria Stefania; Sopkova‐De Oliveira Santos, Jana; Voisin‐Chiret, Anne‐Sophie; et al.
Abstract: Pyridoclax is considered a promising anticancer drug, acting as a protein‐protein interaction disruptor, with potential applications in the treatment of ovarian, lung, and mesothelioma cancers. Eighteen sensibly selected structural analogues of Pyridoclax were synthesized, and their physicochemical properties were systematically assessed and analyzed. Moreover, considering that drug‐membrane interactions play an essential role in understanding the mode of action of a given drug and its eventual toxic effects, membrane models were used to investigate such interactions in bulk (liposomes) and at the air‐water interface. The measured experimental data on all original oligopyridines allowed the assessment of relative differences in terms of physicochemical properties, which could be determinant for their druggability, and hence for drug development. Abstract : The protein‐protein interaction disruptor Pyridoclax is a promising anticancer drug. A set of structural Pyridoclax analogues were synthesized, and their physicochemical properties were systematically assessed and analyzed. Given that drug‐membrane interactions play a key role in understanding a drug's mode of action and its eventual toxic effects, membrane models were used to gauge such interactions both in bulk and at the air‐water interface. The results of this study should aid in the drug development of this compound class.